From Utility to Intention: Unpacking the Drivers of Smart Hotel Adoption in the Digital Native Segment - Octaviany, Vany; Hasyim, Muhamad Ardi Nupi; Gusnadi, Dendi; Mardiyana, Eva (Journal of Tourism, Hospitality and Travel Management, 2023)
As the hospitality industry evolves in tandem with technological advancement, the role of smart technologies in shaping guest experiences and influencing decision-making has become increasingly central. This study investigates how digital natives—consumers born into a digitally connected world—navigate smart hospitality environments by integrating the Technology Acceptance Model (TAM) elements with constructs such as trust in technology, smart hospitality experience, and social media influence. A total of 240 valid responses were collected through a structured online questionnaire targeting individuals aged 18–40 who had experience staying in hotels with smart features and actively engaged with social media during travel planning. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study confirms that perceived ease of use, usefulness, and trust significantly influence purchase intention, with smart hospitality experience as a key mediator. Moreover, social media is powerful in shaping perceptions of technology, trust, and intention. The findings enrich our understanding of how functional, emotional, and social dimensions converge in technology-driven hospitality decisions. This study offers theoretical advancement and managerial insight, highlighting the importance of designing technology for efficiency, experience, trust, and narrative resonance.